One-and-a-half syndrome in ischaemic locked-in state: a clinico-pathological study. - Bogousslavsky, J (1984)
Five patients with "locked-in" syndrome and dysconjugate palsy of horizontal gaze were studied. In all cases internuclear ophthalmoplegia due to dysfunction or destruction of the median longitudinal fasciculus was combined with an ipsilateral gaze palsy, producing the "one-and-a-half" syndrome. Clinical and electro-oculographic examination suggested involvement of the paramedian pontine reticular formation when all ipsilateral saccades were abolished, when exotropia of the contralateral eye was present, and when vestibular stimulation showed full conjugate deviation to the damaged side. Involvement of the abducens nucleus was suggested when the palsy of ipsilateral gaze was not dissociated on vestibular stimulation. In three cases these clinical deductions were confirmed by the pathological study, which showed a corresponding destruction of the median longitudinal fasciculus, paramedian pontine reticular formation and abducens nucleus. In one case the one-and-a-half syndrome evolved into a total horizontal gaze palsy, which corresponded to involvement of the abducens nucleus contralateral to the initially destroyed paramedian pontine reticular formation. Vertical oculocephalic response disappeared, because of destruction of the median longitudinal fasciculus on both sides (bilateral internuclear ophthalmoplegia). Patients with the locked-in syndrome provide a unique situation in which complex pontine oculomotor disturbances may be studied, because consciousness is preserved. In these patients, dissociated and dysconjugate oculomotor palsy may have been underestimated.